Cardiovascular diseases, depression disorders and potential effects of omega-3 fatty acids - Trebatická, Jana; Dukát, Andrej; Ďuračková, Zdeňka; Muchová, Jana (Physiological research, 2017)
Cardiovascular disease (CVD) and depressive disorders (DD) are two of the most prevalent health problems in the world. Although CVD and depression have different origin, they share some common pathophysiological characteristics and risk factors, such as the increased production of proinflammatory cytokines, endothelial dysfunction, blood flow abnormalities, decreased glucose metabolism, elevated plasma homocysteine levels, oxidative stress and disorder in vitamin D metabolism. Current findings confirm the common underlying factors for both pathologies, which are related to dramatic dietary changes in the mid-19th century. By changing dietary ratio of omega-6 to omega-3 fatty acids from 1:1 to 15-20:1 some changes in metabolism were induced, such as increased pro-inflammatory mediators and modulations of different signaling pathways following pathophysiological response related to both, cardiovascular diseases and depressive disorders.
Keywords: dietní tuky; kardiovaskulární nemoci; Depressive Disorder; Oxidative Stress; Signal Transduction; Fatty Acids, Omega-3; omega-3 mastné kyseliny; mediátory zánětu; lidé; Inflammation Mediators; depresivní poruchy; oxidační stres; Cardiovascular Diseases; Dietary Fats; signální transdukce; Humans